CampusPlay: Leveraging Community-Based Digital Innovation to Boost University Students' Sports Engagement - Ammie Aprilliani; Rachmawati Pertiwi Iriani; Dirrie Nabhila Ginting; Asep Taryana (Journal of Educational Management Research, 2026)
This study aims to develop a community-based digital innovation to enhance university students' participation in sports activities. Despite the widespread use of digital technology, students often struggle with limited information, coordination issues, and a lack of collaborative platforms. Using the design thinking approach, the research focuses on the development of the "CampusPlay" application. The study follows the four stages of design thinking: empathize, define, ideate, and prototype, excluding the testing phase. The findings suggest that students require a digital platform to help find sports partners, manage schedules, and implement a deposit-based payment system to improve commitment. The CampusPlay wireframe incorporates key features, such as "Find Partner" and "Create Match," promoting social collaboration and efficient management of campus sports activities. The design thinking methodology proves effective in creating user-centered, community-driven digital solutions that foster social sustainability within the university context.